A hybrid method in the analysis of planar waveguides - Büyükaksoy, A; Birbir, F (Springer-Verlag Berlin, 2000)
A hybrid method consisting of employing the mode matching method in conjunction with the Fourier transform technique is used to analyze an impedance loaded parallel plate waveguide. In contrast to the classical formulation which lead to an intractable matrix Wiener-Hopf equation, the hybrid method that we will adopt reduces the related boundary value problem into a scalar one and permits to bypass the most challenging step of matrix Wiener-Hopf factorization.
NATO Advanced Study Institute on Applied Computational Electromagnetics - State of the Art and Future Trends -- JUL 26-AUG 04, 1997 -- SAMOS, GREECE